The influence of project based learning and learning creativity on student learning outcomes in digital content production materials in grade 8 of smp pelita ciampea - Hartono, Rudi; Adrisdityas Candra Rifani, Salsabila; Jamilah, Siti; Yektyastuti, Resti; Tayfur Ozturk, Omer (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2025)
This study was motivated by the decline in learning quality due to low teacher pedagogical competence and the limited use of technology in the learning process. Initial observations in junior high school computer science classes showed decreased student learning outcomes, particularly in digital content production. This study aims to analyze the effect of Project-Based Learning (PBL) assisted by Artificial Intelligence (AI) on student learning outcomes based on learning creativity levels. Using a quasi-experimental method with a 2x2 factorial design, the study involved eighth-grade students in Bogor City, with achievement tests and creativity questionnaires as instruments. Data were analyzed using two-way ANOVA and Tukey's post-hoc test. Results indicated significant differences in learning outcomes between students using AI-assisted PBL and those without, along with an interaction effect between the learning model and creativity. AI-assisted PBL proved effective in improving digital content learning outcomes, especially for students with high creativity, emphasizing the need for digital teaching tools and student-centered learning design